2015
DOI: 10.1007/s13312-015-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus infection in monozygotic twins with twin-to-twin transfusion syndrome

Abstract: Intrauterine hemodynamics may be important in pathophysiology of congenital cytomegalovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We cannot evaluate chorionicity in this data set; however, the discordance of infection in monochorionic twins leads one to ponder about the epigenetics at play. Twin-twin transfusion syndrome is also noted in two other concordant cases of MZ twins labeled (Griesmaier et al, 2010;Nakajima et al, 2015). In the Nakajima study, the smaller/donor twin was more profoundly affected, while in the Griesmaier study, both twins are affected.…”
Section: Discussionmentioning
confidence: 93%
“…We cannot evaluate chorionicity in this data set; however, the discordance of infection in monochorionic twins leads one to ponder about the epigenetics at play. Twin-twin transfusion syndrome is also noted in two other concordant cases of MZ twins labeled (Griesmaier et al, 2010;Nakajima et al, 2015). In the Nakajima study, the smaller/donor twin was more profoundly affected, while in the Griesmaier study, both twins are affected.…”
Section: Discussionmentioning
confidence: 93%
“…1). Study characteristics appear in Table 2 (11–41). The systematic review included 18 single-case reports, 6 case series, 5 cohort/cross-sectional studies, and 1 pre-post intervention study.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of hearing loss is correlated with CMV viral load (42). Between twins, placental histopathology and amniotic fluid assays have indicated that symptom severity may be associated with viral load in the placenta (22,26), although differential outcomes have been documented in identical twins who shared a monochorionic placenta (25,31). Our review found that each cCMV-positive patient’s odds of hearing loss are tripled if their twin is also infected, which may relate to viral load.…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection in both monochorionic and dichorionic twins can occur in only one fetus or both twins, clinical symptoms and prognosis were quite different ( Table 3 ). In the 21 reported cases of congenital CMV infected twins [2] , [3] , [4] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , 10 cases (47.6%) were single infant infection, of which 3 cases (30%) were stillborn or died after birth, 2 cases (20%) were terminated. 11 cases (52.3%) were infected with both twins, 1 case of them both twins were stillbirths, one of twins in a case died after birth, twins in a case were terminated.…”
Section: Discussionmentioning
confidence: 99%